2017
DOI: 10.1016/j.powtec.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Continuous powder mixing of segregating mixtures under steady and unsteady state regimes: Homogeneity assessment by real-time on-line image analysis

Abstract: Continuous powder processes, such as continuous powder mixing, are more than ever envisioned as a viable alternative to batch equipment, in various industries such as pharmaceuticals, specialty chemicals (zeolites, SiC), bio-renewables or food. In the present work we have implemented an on-line image analysis setup that is able to capture all the images of the particles at the outlet of a continuous pilot-scale mixer. This allows the determination of the homogeneity of mixtures of two different compositions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…17 shows the fine particle content in the five cells at steady-state for the two mixtures. As commented in Ammarcha et al [3], the first four cells are richer in fine particles than the last cell, whatever the conditions under which the blender operates, pointing out the presence of a segregation effect. As for the coarse product alone, it can be shown that the steady hold-up weight of the mixture in each cell can be assimilated to that of coarse couscous, which means that (Eq.…”
Section: Derivation Of a Non-homogeneous Modelmentioning
confidence: 70%
See 2 more Smart Citations
“…17 shows the fine particle content in the five cells at steady-state for the two mixtures. As commented in Ammarcha et al [3], the first four cells are richer in fine particles than the last cell, whatever the conditions under which the blender operates, pointing out the presence of a segregation effect. As for the coarse product alone, it can be shown that the steady hold-up weight of the mixture in each cell can be assimilated to that of coarse couscous, which means that (Eq.…”
Section: Derivation Of a Non-homogeneous Modelmentioning
confidence: 70%
“…Part of the presented work will deal with mixtures of fine and coarse couscous. The analysis of these will be performed on-line by an image analysis ring that has been fully presented in Ammarcha et al [3]. A belt conveyor is placed at the mixer's outlet so as to form a single layer of particles by adjusting its speed to the inflow rate considered.…”
Section: Mixture Composition Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Optical methods typically have high spatial and temporal resolutions that allow these methods to be readily extended to advanced methods such as PIV or particle tracking velocimetry (PTV) [35]. As such, optical methods are found extensively in lab scale systems [36] and easily extendable to pilot scale systems [37]. The greatest limitation of the digital imaging techniques however, is that only wall or surface phenomenon can be investigated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Basically, the idea is to develop and industrialise, either on-line techniques or in-situ techniques for measuring powder blend homogeneity during processing, and use this directly for product validation. For this, electrical methods -such as capacitance-can be used (Ehrhardt et al [11]), but also image analysis (Muerza et al [12], Berthiaux et al [13], Ammarcha et al [14]), NIR spectroscopy (Hailey et al [15]; Koller et al [16]; Martinez et al [17]; Vanarase et al [18]), FT-Raman (Vergote et al [19], De Beer et al [20]), Laser Induced Fluorescence (Lai et al [21]), NIR chemical imaging, etc. Of course, because of mixtures variety, there is not a single technique able to treat all the cases, and not all the methods cited have the same running price.…”
Section: Short-term Evolutions On-line Measurement For Assessing Homomentioning
confidence: 99%